2022
DOI: 10.1161/circimaging.121.013745
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Extracellular Volume in Cardiac Magnetic Resonance Without Blood Sampling: a Reliable Tool to Replace Conventional Extracellular Volume

Abstract: BACKGROUND: The calculation of extracellular volume (ECV) in cardiac magnetic resonance requires hematocrit, limiting its applicability in clinical practice. Based on the linear relationship between hematocrit and blood T1 relaxivity, a synthetic ECV could be estimated without a blood sample. We aim to develop and test regression models for synthetic ECV without blood sampling in 1.5-T and 3.0-T scanners. METHODS: A total of 1101 subjects who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Die MRT kann dabei mithilfe von nativen und kontrastmittelverstärkten T1-Maps auch das extrazelluläre Volumen des Myokards quantifizieren. Dieses ist bei Amyloidinfiltration stark erhöht [47] und kann zuverlässig mit der MRT bestimmt werden [48]. Die Klassifizierung der ATTR-Amyloidose von der AL-Form wird klinisch noch nicht routinemäßig mit der Kardio-MRT durchgeführt.…”
Section: Kardiale Amyloidoseunclassified
“…Die MRT kann dabei mithilfe von nativen und kontrastmittelverstärkten T1-Maps auch das extrazelluläre Volumen des Myokards quantifizieren. Dieses ist bei Amyloidinfiltration stark erhöht [47] und kann zuverlässig mit der MRT bestimmt werden [48]. Die Klassifizierung der ATTR-Amyloidose von der AL-Form wird klinisch noch nicht routinemäßig mit der Kardio-MRT durchgeführt.…”
Section: Kardiale Amyloidoseunclassified
“…65 A simplified approach for the assessment of ECV is introduced where the hematocrit can be estimated from native values of blood pool T1 (“synthetic ECV”). 66,67 The development of 3D T1-mapping acquisition are explored in 3D ECV quantification. 68…”
Section: Contrast-enhanced Techniquesmentioning
confidence: 99%
“…65 A simplified approach for the assessment of ECV is introduced where the hematocrit can be estimated from native values of blood pool T1 ("synthetic ECV"). 66,67 The development of 3D T1-mapping acquisition are explored in 3D ECV quantification. 68 ECV has been shown to be elevated in EMB-proven acute myocarditis, correlating with edema, and in subclinical myocardial disease in rheumatoid arthritis, systemic lupus erythematosus, and systemic sclerosis, likely representing low-grade inflammation and diffuse fibrosis.…”
Section: T Myo T Myo T Blood T Blood Postgd N Ative Postgd N Nativementioning
confidence: 99%
“…Based on the linear relationship between the hematocrit and the native T1 of blood, synthetic ECV is a new method to determine ECV without blood sampling ( 116 ). Recently, a large cohort study showed synthetic ECV presented no statistical difference from conventional ECV estimated by CMR and measured ECV by histological examination ( 117 ).…”
Section: Detection: Laboratory Biomarkers and Imaging Techniquesmentioning
confidence: 99%